A FUZZY GRA-BASED DECISION-MAKING APPROACH ON THE SELECTION OF LEAN TOOLS: A CASE STUDY OF INDIAN APPAREL INDUSTRY - Manickam, Bhuvanesh Kumar; Rathinasamy, Parameshwaran (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Most manufacturing industries find many Non-Value-Added (NVA) components compared to value-added components from their shop floor. Identifying the best Lean Tools (LTs) from many available tools for their present manufacturing environment considering many wastes remains a multi-criteria decision-making problem. The problem becomes complicated when decision-makers' preference for wastes and LTs is uncertain. Grey theory is the most predominant mathematical method to address this issue. This paper proposed a framework that incorporates value stream mapping (VSM) and grey relational analysis coupled with principal component analysis under fuzzy environment for LTs selection problem. The VSM of the current and future state are compared to visualize the improvement. The framework developed in this work is illustrated in a case study from the Indian apparel industry. The results show a significant reduction in production lead time (62.5%), cycle time (2.3%), NVA time (62.6%), and the number of workers (16.6%).